Cadmium Exposure and Risk of Pancreatic Cancer: A Protocol of Systematic Review and Meta-analysis - Soleimani, Yaser; Mahmoudi, Sheyda; Daraei, Mahdi; varseh, Mahdieh; Khalafi, Fatemeh; Jahazi, Mohammad Amin; Khorsand, Soroush; Yadollahi Farsi, Maryam; Soleimani, Mahna; Aryanejad, Ali; et al. (Asian Pacific Journal of Environment and Cancer, 2024)
Background: Pancreatic cancer is a devastating disease with a poor prognosis, and its etiology involves a complex interplay of genetic, environmental, and lifestyle factors. Among environmental factors, cadmium, a toxic heavy metal, has been implicated in carcinogenesis and is found in various industrial processes, tobacco smoke, and certain foods. Previous studies examining the association between cadmium exposure and pancreatic cancer risk have reported inconsistent findings, necessitating a systematic review and meta-analysis to clarify this relationship. Methods: A systematic search was conducted following PRISMA guidelines to identify relevant studies from electronic databases, including PubMed, Embase, Web of Science, Cochrane Library, Scopus, and Google Scholar. Eligible studies included observational designs (cohort, case-control, cross-sectional) that investigated the association between cadmium exposure and pancreatic cancer risk in human populations. Data extraction, risk of bias assessment, and meta-analysis were conducted using established protocols. Subgroup analyses were performed based on study characteristics and exposure assessment methods. Results: The systematic review and meta-analysis included a comprehensive assessment of the existing literature on cadmium exposure and pancreatic cancer risk. Pooled analysis of eligible studies revealed a potential association between cadmium exposure and an increased risk of pancreatic cancer. However, the magnitude and consistency of this association varied across studies, highlighting the complexity of environmental exposures and their impact on cancer risk. Subgroup analyses and sensitivity analyses were conducted to explore sources of heterogeneity and assess the robustness of the results. Conclusion: This systematic review and meta-analysis contribute to the current understanding of the relationship between cadmium exposure and pancreatic cancer risk. While the findings suggest a potential association, further research is needed to elucidate the underlying mechanisms and clarify the role of cadmium in pancreatic carcinogenesis. These results underscore the importance of environmental risk factors in cancer development and highlight the need for public health interventions aimed at reducing cadmium exposure and improving cancer prevention strategies.